1989
DOI: 10.1080/01140671.1989.10428030
|View full text |Cite
|
Sign up to set email alerts
|

Soil water measurements on four alluvial soils in Canterbury 1. Soil water extraction patterns under spring-sown peas and barley, and pasture

Abstract: Changes in water content of four soil types from alluvium were monitored under springsown barley during 1978/79, spring-sown peas during 1979/80 and under pasture during September 1981-August 1984. The soil types varied in texture and depth to sandy gravels and are representative of a large area of the Canterbury and North Otago Plains. Patterns of soil water depletion over time are depicted graphically for representative soils in each season. All crops extracted similar amounts of water from the upper 30 cm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…More detailed records of the previous history of the paddock, methodology, and soil descriptions are given in Webb (1989).…”
Section: Methodsmentioning
confidence: 99%
“…More detailed records of the previous history of the paddock, methodology, and soil descriptions are given in Webb (1989).…”
Section: Methodsmentioning
confidence: 99%
“…Field studies have shown that site-specific in-season adjustments of fertiliser inputs to account for climatic conditions and varying yield potential differences increase fertiliser nitrogen (N) use efficiency up to 368% compared with common farmer practices. 5,6 Before the introduction of precision agriculture methods, researchers had noted soil variability 7,8 and discussed the need for differential inputs, e.g. fertiliser application to hill country.…”
Section: Introductionmentioning
confidence: 99%
“…Before the introduction of precision agriculture methods, researchers had noted soil variability and discussed the need for differential inputs, e.g. fertiliser application to hill country .…”
Section: Introductionmentioning
confidence: 99%